Interactive Software for the Learning of Mathematics in Elementary School Students in the Province of Tungurahua - Sánchez Sánchez, Paulina (2022)
This article shows a study on the impact of the development of a video game for the teaching of mathematics in elementary school students, developed mainly to strengthen knowledge as a new educational resource for teachers to give interactive classes changing the usual way in which they teach, which would cause the student’s interest in learning. The methodology used was based on three phases: first, exploratory research was carried out in the Gabriela Mistral institution in San Pedro de Pelileo (Ecuador), second, the video game was developed with an agile methodology, applying an adaptive algorithm in its architecture that helps the children’s knowledge to be modified through the game, expanding the knowledge information they have. Finally, a determined group of students was evaluated to know whether or not the game contributed to their education and it was found that an increase of 27.78% was achieved in their knowledge, in relation to the levels they had with the conventional learning method.